Migration patterns: two little magazines of 1960–1962. Issue 2 (23rd February 2017) - Goddard, Louis
ABSTRACT: This article investigates the legacy of the short-lived but influential little magazine Migrant (1959–1960), considering the extent to which two subsequent publications – Mica and Satis (both 1960–1962) – inherited its contributors, style and poetic preoccupations. Through an approach combining traditional literary and textual history and data-driven social network analysis, Mica and Satis are placed side by side, offering a dual perspective on the British and North American poetic avant gardes in the early 1960s. The British poet J.H. Prynne is identified as representative of a younger generation of poets who came into contact with the Migrant legacy through these secondary publications, and his contributions to the scene, both intellectual and organisational, are considered in detail. The practical aspects of magazine production are examined on the same level as the artistic ones in a provisional effort to establish a more holistic conception of the form, seeing little magazines not just as preliminary receptacles for poetic work but as distinct forms of practice in their own right.